2020
DOI: 10.3389/fimmu.2020.02089
|View full text |Cite
|
Sign up to set email alerts
|

Mumps Outbreaks in Vaccinated Populations—Is It Time to Re-assess the Clinical Efficacy of Vaccines?

Abstract: History illustrates the remarkable public health impact of mass vaccination, by dramatically improving life expectancy and reducing the burden of infectious diseases and co-morbidities worldwide. It has been perceived that if an individual adhered to the MMR vaccine schedule that immunity to mumps virus (MuV) would be lifelong. Recent mumps outbreaks in individuals who had received two doses of the Measles Mumps Rubella (MMR) vaccine has challenged the efficacy of the MMR vaccine. However, clinical symptoms, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 247 publications
(390 reference statements)
1
37
0
1
Order By: Relevance
“…Recent mumps outbreaks in individuals who had received two doses of MMR vaccine have challenged the efficacy of the MMR vaccine. However, clinical symptoms, 5 Journal of Immunology Research complications, viral shedding, and transmission associated with mumps infection have been shown to be reduced in vaccinated individuals, demonstrating a benefit of this vaccine [16]. There was no significant difference among the cases without MuCV in the 2006-2010 birth cohorts (χ 2 = 8:22, p = 0:084); it showed that the sampling was balanced between birth years.…”
Section: Discussionmentioning
confidence: 95%
“…Recent mumps outbreaks in individuals who had received two doses of MMR vaccine have challenged the efficacy of the MMR vaccine. However, clinical symptoms, 5 Journal of Immunology Research complications, viral shedding, and transmission associated with mumps infection have been shown to be reduced in vaccinated individuals, demonstrating a benefit of this vaccine [16]. There was no significant difference among the cases without MuCV in the 2006-2010 birth cohorts (χ 2 = 8:22, p = 0:084); it showed that the sampling was balanced between birth years.…”
Section: Discussionmentioning
confidence: 95%
“…Recent findings in the literature highlighted that mumps outbreaks can occur in heavily vaccinated populations, such as HCWs, and mainly in young adults. Many factors have been considered to explain mumps outbreaks in those highly vaccinated populations: heterogeneous vaccine uptake and primary and secondary vaccine failure (immune escape and waning vaccine-induced immunity) [31].…”
Section: Discussionmentioning
confidence: 99%
“…Waning vaccine-induced immunity accounts for the fall in vaccine immunity over time, determining an inadequate immune response, that leads to virus spread, making adults at higher risk to be infected than children. Potential waning immunity has been reported in recent mumps outbreaks that occurred in Europe that involved young adults who received two doses in childhood [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last decade, again several mumps outbreaks have been reported, especially among vaccinated young adults. Waning of vaccine-induced immunity is considered to play a central role in the re-emergence of mumps among vaccinated young adults [ 1 , 2 , 3 , 4 , 5 ]. However, antigenic differences between the currently circulating wild-type viruses and the vaccine virus may further lead to reduced vaccine-induced immunity.…”
Section: Introductionmentioning
confidence: 99%